Vaginal birth after previous caesarean section in women at Al-Wahda hospital Derna, Libya - Ajroud, Soad; Elzahaf, Raga A.; Arhaiam, Fawzia A. G. (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2021)
Background: Vaginal birth after caesarean section is one strategy that has been developed to decrease the rate of caesarean section. Methods: The prospective observational study was carried out over a period of 01 January 2017 to 31 December 2018 years. VBAC was routinely offered at Al-Wahda hospital Derna to women fulfilling the criteria for trial of scar, according to the hospital protocol. Results: A total of 5018 deliveries took place in the study duration, there were 1039 (20.7%) had previous one caesarean section, out of which 319 (30.7%) were the number of underwent repeat caesarean section and 720 (69.3%) were the number of VBAC. The indications for emergency repeat caesarean section at Al-Wahda hospital was (29.3%) malpresentation, (24.45%) FD, (13.47) postdate, (11.59) obstracted lab and abruptiopl (5.95%). Anemia and difficult intubation were observed in repeated caesarean section. Conclusions: This study concluded that there is a high chance of success in a trial of labor. These findings might help clinicians and women in the decision-making for the mode of delivery when it comes to pregnancy with a previous caesarean section. Women are explained about the option of trial of scar and told about the risk associated with a repeat CS, so many CSs can be avoided.